Cover Feature: Fluorescent Nitric Oxide Photodonors Based on BODIPY and Rhodamine Antennae (Chem. Eur. J. 47/2019). Issue 47 (15th July 2019) - Parisi, Cristina; Failla, Mariacristina; Fraix, Aurore; Rolando, Barbara; Gianquinto, Eleonora; Spyrakis, Francesca; Gazzano, Elena; Riganti, Chiara; Lazzarato, Loretta; Fruttero, Roberta; Gasco, Alberto; Sortino, Salvatore
Abstract : Photoactivation of two novel BODIPY and Rhodamine‐based molecular hybrids with the highly biocompatible green light triggers the NO release from the nitroso aniline‐derivative appendages without precluding the typical green and orange‐green fluorescence emission of the antennae units, making them intriguing systems for image‐guided phototherapeutic applications where the controlled delivery of NO is required. More information can be found in the Full Paper by L. Lazzarato, S. Sortino, et al. onpage 11080 .